Pathways of emplacement and belonging of the Turkiyeli population in North Cyprus: insights from a settler village - Zrilli, Aysenur Talat (Routledge Journals, Taylor & Francis Ltd, 2024)
This article focuses on the 1975-1980 migration from Turkey to North Cyprus, which was conjointly facilitated by Turkish and Turkish Cypriot states. It seeks to contribute to the academic literature on the incorporation experiences of the subjects of this policy, that is, the 'Turkiyeli' groups living in the island's north. In an attempt to underline the heterogeneous migration experiences of this population, the article depicts different incorporation strategies of two groups residing in a settler village. Drawing on field observations and in-depth interviews, it argues that the distinctive pathways of emplacement and belonging of the groups under scrutiny had taken shape in accordance with their distinctive strategies of mobilizing, validating and creating social and cultural capital.
Keywords: Immigrant incorporation; social capital; cultural capital; North Cyprus; Turkish migrants; Turkish settlers